Effect of gastric juice on the surface, optical, and mechanical properties of different computer-aided design/computer-aided manufacturing dental ceramics: A systematic review and meta-analysis - Silva, Lorena Scaion [UNESP]; Bento, Victor Augusto Alves [UNESP]; Cruz, Kevin Henrique [UNESP]; Nascimento, Victor Alves [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Wolters Kluwer, 2025)
Purpose: Effect of an erosive challenge on the surface, optical, and mechanical properties of prostheses manufactured using different types of dental ceramics for computer-aided design/computer-aided manufacturing (CAD/CAM). Materials and Methods: Protocol followed PRISMA guidelines. A PICO question was formulated: 'What is the effect of gastric juice on the surface, optical and mechanical properties of different types of dental ceramics made using the CAD/CAM system?.' PubMed/MEDLINE, EMBASE, Web of Science, Scopus, Cochrane Library, and ProQuest was search to July 2024. The quality of the full-text articles was evaluated for Joanna Briggs Institute critical. The meta-analysis was the inverse variance method (P < 0.05). Results: After applying the selection criteria, 15 in vitro studies published between 2014 and 2022, 777 specimens were included. Fourteen studies were included in meta-analysis, which no significant difference in the surface roughness after the erosive challenge was observed between the ceramic types (P = 0.59; MD: 0.14; 95% confidence interval [CI]: -0.36-0.64; I 2 = 86%, P < 0.01), significantly less color change was observed without the erosive challenge (P < 0.05; MD: 1.82; 95% CI: 0.86-2.79; I 2 = 81%, P < 0.01), and significantly lower microhardness was observed for the groups with the erosive challenge (P = 0.03; MD: -0.95; 95% CI: -1.82 - 0.08; I 2 = 88%, P < 0.01). Conclusions: The ceramics showed changes in roughness, color stability, microhardness and flexural strength, depending on the type of ceramic.
Keywords: ceramics; color; Computer-aided design-computer-aided manufacturing; erosion; mechanical tests